Biomedical Engineering As A Catalyst For Healthcare Quality, Safety, And Technology Integration: A Comprehensive Review (The Review of Diabetic Studies, 2025)
Biomedical engineering has emerged as a transformative force in modern healthcare, serving as a bridge between medical science, engineering innovation, and hospital systems to improve patient care outcomes. This comprehensive review examines the critical role of biomedical engineering in enhancing healthcare quality, ensuring patient safety, and driving the integration of advanced technologies into clinical practice. Through innovations such as smart medical devices, diagnostic imaging systems, artificial intelligence (AI), robotics, and telemedicine platforms, biomedical engineers are redefining how healthcare is delivered, monitored, and optimized. The review explores how engineering solutions contribute to reducing medical errors, supporting evidence-based decision-making, and improving the reliability and safety of medical equipment. It further highlights the importance of biomedical engineering in building resilient healthcare systems capable of adapting to digital transformation, regulatory demands, and patient-centered care models. Challenges such as cybersecurity risks, interoperability issues, cost barriers, and workforce readiness are critically analyzed to present a balanced perspective. The findings demonstrate that biomedical engineering is not only a technological enabler but also a strategic catalyst for achieving healthcare goals aligned with global standards and national health visions. This review concludes by emphasizing the need for stronger system-level integration and policy support to maximize its benefits for future healthcare innovation.